The Impact of Business Ethics on Business Turnover by Application to Amazon for Online Shopping - Mustafa, Amal Mohamed Mohamed (The Arab Journal of Administration, 2024)
In order for today’s organizations to be able to compete successfully in the world of business and advance both in the internal and external environment, they must prepare an effective human element who has the competence, skill, and distinction that will enable them to compete successfully. This will only be possible by adhering to ethical principles. Therefore, this study focused on knowing The impact of business ethics on the turnover rate in the application to (Amazon e-commerce company), which is a multinational company. The study population was determined from customer service employees at their various job levels, and the questionnaire was conducted on a sample of employees at Amazon, the target community, and the researcher relied on a random sample (30) responses were collected through a Google Form link. They were processed using the SPSS statistical software package. The researcher used statistical methods appropriate to the study’s questions and hypotheses, including descriptive and inferential statistics. The study concluded that there is a relationship between work ethics and the rate of turnover among employees at Amazon e-commerce company. The results of the study concluded that there is a positive relationship with statistical significance between the dimensions of the study, which are as follows: There is a significant effect of work ethics on the turnover rate. There is a significant impact of compliance with laws and regulations on the turnover rate. There is a significant effect of fairness and non-discrimination among employees on the turnover rate. There is a significant effect of integrity and transparency on the turnover rate. There is a significant effect of proficiency in completing work on the turnover rate. Then the researcher concluded this study with a number of recommendations, including the necessity of involving the organization’s employees in the program for developing the ethical charter and organizational culture. The importance of integrating the organization’s ethical charter into a computer program as an information system, and linking it to an internal network for easy access to information and making sound decisions.